2006
DOI: 10.1359/jbmr.060314
|View full text |Cite
|
Sign up to set email alerts
|

Teriparatide Increases Bone Formation in Modeling and Remodeling Osteons and Enhances IGF-II Immunoreactivity in Postmenopausal Women With Osteoporosis

Abstract: Transiliac bone biopsies were obtained from 55 women treated with teriparatide or placebo for 12-24 months. We report direct evidence that modeling bone formation at quiescent surfaces was present only in teriparatide-treated patients and bone formation at remodeling sites was higher with teriparatide than placebo.Introduction: Recombinant teriparatide [human PTH(1-34)], a bone formation agent for the treatment of osteoporosis when given once daily subcutaneously, increases biochemical markers of bone turnover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
150
1
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 210 publications
(174 citation statements)
references
References 50 publications
19
150
1
4
Order By: Relevance
“…Histomorphometric analyses in humans have demonstrated that the increases in bone-forming surfaces with PTH treatment were primarily through remodeling-based mechanisms in short- (19) and longer-term studies. (20) Examination of the impact of sclerostin inhibition on bone resorption and bone modeling warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Histomorphometric analyses in humans have demonstrated that the increases in bone-forming surfaces with PTH treatment were primarily through remodeling-based mechanisms in short- (19) and longer-term studies. (20) Examination of the impact of sclerostin inhibition on bone resorption and bone modeling warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…(34,35) During the second half of the study, the anabolic effect in the combination group occurred with increased bone remodeling, with formation and resorption marker levels above baseline. (6) One of the potential limitations of PTH treatment is that its stimulatory effect on intracortical bone remodeling can increase cortical porosity. This may not translate into decreased mechanical strength, however, because the porosity is concentrated at the endocortical surface (close to the neutral axis of bone) and may be offset by increased periosteal apposition and increased cortical thickness.…”
Section: Discussionmentioning
confidence: 99%
“…(1)(2)(3)(4) Unlike the bisphosphonates, which reduce bone remodeling, teriparatide is an anabolic agent that stimulates bone formation and increases bone remodeling. (4) While both classes of agents improve bone mineral density (BMD) and reduce fracture risk, teriparatide also improves the microarchitecture of cancellous and cortical bone in the iliac crest, (5)(6)(7) providing even greater improvements in bone strength (as measured by finite-element analysis) than those observed with antiresorptive agents alone. (4,8,9) In one head-to-head comparison of alendronate and teriparatide in patients with glucocorticoid-induced osteoporosis, vertebral fracture (but not nonvertebral fracture) incidence was lower with teriparatide than with alendronate.…”
Section: Introductionmentioning
confidence: 99%
“…Increased bone formation is manifested as early as 28 days as evidenced by a rise in the level of circulating markers of osteoblast function, and an increase in tetracycline-labeled surface in transileal biopsies [7][8][9]. By 6 months, indices of bone resorption have also increased [1,9].…”
Section: Introductionmentioning
confidence: 99%